1998
DOI: 10.1161/01.str.29.8.1595
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Organization in the Branching Region of Human Brain Arteries

Abstract: Background and Purpose-Unruptured saccular aneurysms are relatively common, occurring in 4% to 9% of autopsies.Their development at the apex region of brain artery bifurcations is attributed to a combination of structural factors and the effect of blood pressure. Collagen is a primary tension-bearing fabric of the vessel wall, and our purpose was to examine its 3-dimensional alignment at arterial branches. Methods-Sixteen segments of arteries from the circle of Willis, including bifurcations, were pressure dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 33 publications
4
80
1
1
Order By: Relevance
“…Previous studies suggested that the bifurcation apex may be protected from hemodynamic stresses by a narrow band of densely packed collagen fibers that covers the bifurcation medial pad and provides strength and stiffness to the region. 2,5,21 It was shown using surgically created arterial bifurcations in animals that the acceleration region adjacent to the medial pad was characterized by disrupted internal elastic lamina and loss of endothelium, which is consistent with early-stage IAs. 17 Whereas our simulations showed that the acceleration area grew from 0.38 mm to almost 7 mm with a larger angle, the medial pad was reported to take values between 0.42 mm 2 and 1.40 mm 2 .…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies suggested that the bifurcation apex may be protected from hemodynamic stresses by a narrow band of densely packed collagen fibers that covers the bifurcation medial pad and provides strength and stiffness to the region. 2,5,21 It was shown using surgically created arterial bifurcations in animals that the acceleration region adjacent to the medial pad was characterized by disrupted internal elastic lamina and loss of endothelium, which is consistent with early-stage IAs. 17 Whereas our simulations showed that the acceleration area grew from 0.38 mm to almost 7 mm with a larger angle, the medial pad was reported to take values between 0.42 mm 2 and 1.40 mm 2 .…”
Section: Discussionmentioning
confidence: 75%
“…Specifically, in human arterial walls the collagen fibers are not perfectly aligned but are dispersed around a mean direction. Such a fiber dispersion has been observed in, for example, human arterial walls [1][2][3][4][5], the myocardium [6,7], corneas [8,9] and articular cartilage [10]. In particular, recent extensive experimental results [4] have shown that the collagen fiber dispersion in each of the layers of (healthy) human thoracic and abdominal aortas and iliac arteries is non-symmetric, in contrast to the rotationally symmetric fiber dispersion assumed in previous studies; see, for example, [11].…”
Section: Introductionmentioning
confidence: 80%
“…Through this, the inner layers of the arterial wall would bulge and then form an aneurysm. But it was demonstrated that these gaps are equally common in patients with and without aneurysms (Stehbens 1989) and usually packed by dense collagen fibrils (Fujimoto 1996;Finlay et al 1998). Furthermore, the defect in the muscle layer is located in the wall of the aneurysmal sac and not at the neck of the aneurysm (Stehbens 1989).…”
Section: Pathology Epidemiology and Etiologymentioning
confidence: 99%